2018
DOI: 10.1051/matecconf/201821501034
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of mechanical properties of clay brick for masonry wall in Indonesia

Abstract: In principle, the main construction of the non-engineered building in Indonesia is the wooden structure. It can be seen from traditional houses in Indonesia. However, In the last two centuries, the use of brick masonry as wall component has been becoming the primary material. Another side, some places in Indonesia are the seismic areas and earthquake-prone areas. Learning from the earthquake that has happened in the last ten years, the building that used clay brick for masonry wall mostly suffered damage and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The moulded dough is then dried in the sun for several days. After drying, the bricks are taken to the brick kiln, which is burned manually with firewood without temperature control [18]. The overburning results in a byproduct that called clinker brick (Fig.…”
Section: Clinker Brick Wastementioning
confidence: 99%
“…The moulded dough is then dried in the sun for several days. After drying, the bricks are taken to the brick kiln, which is burned manually with firewood without temperature control [18]. The overburning results in a byproduct that called clinker brick (Fig.…”
Section: Clinker Brick Wastementioning
confidence: 99%
“…Research conducted by Juliafad [11] showed that compressive strength distribution in red bricks in West Sumatra had a maximum value of 3 MPa. Ridwan [12] also concluded that the mechanical properties of bricks in West Sumatra did not meet SNI requirements. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In the making process the bricks should be easily printed, dried without shrinkage and produced without any cracks or curves. Investigating the physical changes in the making process of the bricks have been conducted by several researchers [1,2,3].…”
Section: Introductionmentioning
confidence: 99%